The effect of renal replacement therapy and antibiotic dose on antibiotic concentrations in critically ill patients: data from the multinational sampling antibiotics in renal replacement therapy study - Roberts, Jason A.; Joynt, Gavin M.; Lee, Anna; Choi, Gordon; Bellomo, Rinaldo; Kanji, Salmaan; Mudaliar, M Yugan; Peake, Sandra L; Stephens, Dianne; Taccone, Fabio Silvio; Ulldemolins, Marta; Valkonen, Miia Maaria; et al. (Oxford University Press for the Infectious Diseases Society of America, 2020)
Background: The optimal dosing of antibiotics in critically ill patients receiving renal replacement therapy (RRT) remains unclear. In this study, we describe the variability in RRT techniques and antibiotic dosing in critically ill patients receiving RRT and to relate observed trough antibiotic concentrations to optimal targets. Methods: We performed a prospective, observational, multi-national, pharmacokinetic study in 29 intensive care units from 14 countries. We collected demographic, clinical and RRT data. We measured trough antibiotic concentrations of meropenem, piperacillin-tazobactam and vancomycin and related them to high and low target trough concentrations. Results: We studied 381 patients and obtained 508 trough antibiotic concentrations. There was wide variability (4-8 fold) in antibiotic dosing regimens; RRT prescription, and estimated endogenous renal function. The overall median estimated total renal clearance (eTRCL) was 50 mL/min (interquartile range [IQR] 35-65) and higher eTRCL was associated with lower trough concentrations for all antibiotics (p<0.05). The median (IQR) trough concentration for meropenem was 12.1 mg/L (7.9-18.8), piperacillin 78.6 mg/L (49.5-127.3), tazobactam 9.5 mg/L (6.3-14.2) and vancomycin 14.3 mg/L (11.6-21.8). Trough concentrations failed to meet optimal higher limits in 26%, 36%, 72%, and optimal lower limits in 4%, 4%, and 55% of patients for meropenem, piperacillin and vancomycin respectively. Conclusions: In critically ill patients treated with RRT, antibiotic dosing regimens, RRT prescription and eTRCL varied markedly and resulted in highly variable antibiotic concentrations that failed to meet therapeutic targets in many patients.